Innovative Antibiofilm Smart Surface against Legionella for Water Systems - Simona Filice; Emanuele Luigi Sciuto; Silvia Scalese; Giuseppina Faro; Sebania Libertino; Domenico Corso; Rosario Manuel Timpanaro; Pasqualina Laganà; Maria Anna Coniglio (Microorganisms, 2022)
Legionella pneumophila contamination of water systems is a crucial issue for public health. The pathogen is able to persist in water as free-living planktonic bacteria or to grow within biofilms that adhere to and clog filters and pipes in a water system, reducing its lifespan and, in the case of hospital buildings, increasing the risk of nosocomial infections. The implementation of water management is considered to be the main prevention measure and can be achieved from the optimization of water system architecture, notably introducing new materials and strategies to contrast Legionella biofilm proliferation and so prolong the water system functionality. In this research, we propose a new smart surface against L. pneumophila biofilm formation. This is based on an innovative type of coating consisting of a sulfonated pentablock copolymer (s-PBC, commercially named Nexar™) deposited on top of a polypropylene (PP) coupon in a sandwich filter model. The covering of PP with s-PBC results in a more hydrophilic, acid, and negatively charged surface that induces microbial physiological inhibition thereby preventing adhesion and/or proliferation attempts of L. pneumophila prior to the biofilm formation. The antibiofilm property has been investigated by a Zone of Inhibition test and an in vitro biofilm formation analysis. Filtration tests have been performed as representative of possible applications for s-PBC coating. Results are reported and discussed.